Numerical Analysis on Added Resistance of a Crew Boat with Variation of Wave Period - Dita Adhelia Putri; Muhammad Hafiz Nurwahyu Aliffrananda; Sugeng Riyadi; Sutiyo Sutiyo; I Ketut Aria Pria Utama (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Crew boat is a type of vessels used for the mobility of offshore workers and logistical supply needed for the offshore platform. Crew boat KCT-1901 is categorized as a planning boat with hard chine body. KCT-1901 requires an added power when it is sailing through a seaway. The reason behind this is because when a ship sails through a seaway, the ships experienced a heave and pitch motion resulted in added resistance and hence added power. The goal of the investigation is to estimate added resistance and added power of the crew boat using computational fluid dynamic (CFD) method and tested in calm water and in waves with several Froude numbers (Fr) and wave periods. A method developed by Savitsky is used for verification at high-speed mode. The largest total resistance using CFD in calm water is 38.98 kN and using Savitsky method is 39.00 kN obtained at Fr 0.72. Both are in good agreement and the discrepancy is less than 0.1%. Comparative study was carried out against experimental test in a towing tank. The drag forces tested at Fr 0.12 and 0.24, between the two approaches, showed a discrepancy of about 4%. Further CFD test was conducted on wave pattern analysis, which demonstrated that as the Fr increases the becomes clearer and stronger and tests in waves condition at lower wave period showed that the transverse wave becomes more apparent. Therefore, overall can be said that the CFD simulation showed such a good agreement with empirical Savitsky method and experimental tank test.